Belajar, pembelajaran, dan pendekatan pembelajaran - Rohmah, Ayyu Nur (Maliki Interdisciplinary Journal, 2025)
Studying adn Learning are related to each other. Studying and learning are very important activities in education. Studying is defined as a proscess that allows the emergence or change in behavior that is not caused by maturity or the formation of a primary response. Educatinal and psychological experts consider change as a source of a consistent, effective, positive, and purposeful behavior, which can occur in a variety of situations. Learning includes the design, implementation and evaluation processes. Learning is a process where student interact with teachers and learning resources in the learning environment. The assistance provided by teachers allows student to again systematic and systemic process or activity that is interactive and communicative between teachers and student. Learning is a term that to student interactions in the learning environment between teachers and learning resources. Therefore, how effective a learning process is determined by how well these there elements work together.